Variations of malaysian sea level due to northeast monsoons and southwest monsoons seasons during the El Nino and La Nina events - Noor Baharim Hashim, author; Anie Raflikha Abd. Malek, 1978-, author; Ecomod 2007 (2007 : Pulau Pinang)i (Skudai : Universiti Teknologi Malaysia, 2007)
PRZSL